Action research on improving network deliver speed to recover and retain customers - Rebullida, Carlos III Gomez (Animo Repository, 2023)
Abstract: This paper aims to establish how Ninjavan Philippines Operations Unit will improve its parcel delivery or network speed in order to retain and attract new customers and improve on its reputation. Guided by the cycle of the Plan-Do-Act-Check or PDCA, this action research will first deep dive into the reasons why Ninjavan is suffering an exodus of customers and volume and try to determine what next steps to take to get these volumes back. The first cycle revolves around showing data on showing the period of volume declines and trying to figure out how to stop the bleeding of customers. The second cycle will tackle areas of improvement and how Ninjavan will be trying to win back volumes. This action research will analyze how network speed has an effect on how customers perceive your service to be.